2015
DOI: 10.1186/s13071-015-1061-5
|View full text |Cite
|
Sign up to set email alerts
|

Hemozoin “knobs” in Opisthorchis felineus infected liver

Abstract: BackgroundHemozoin is the pigment produced by some blood-feeding parasites. It demonstrates high diagnostic and therapeutic potential. In this work the formation of co-called hemozoin “knobs” – the bile duct ectasia filled up by hemozoin pigment - in Opisthorhis felineus infected hamster liver has been observed.MethodsThe O. felineus infected liver was examined by histological analysis and magnetic resonance imaging (MRI). The pigment hemozoin was identified by Fourier transform infrared spectroscopy and high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…The parasites detoxify this waste product by biocrystallization with the enzyme heme oxygenase, which breaks down heme into iron, biliverdin and carbon monoxide . The paramagnetic effect of hemozoin in the liver is strong enough to be detected by MRI .…”
Section: Iron Compounds and Their Susceptibilitymentioning
confidence: 99%
“…The parasites detoxify this waste product by biocrystallization with the enzyme heme oxygenase, which breaks down heme into iron, biliverdin and carbon monoxide . The paramagnetic effect of hemozoin in the liver is strong enough to be detected by MRI .…”
Section: Iron Compounds and Their Susceptibilitymentioning
confidence: 99%
“…33 Hamsters were housed three to a cage (OptiRAT) under conventional conditions and were fed with stock diet and water ad libitum. The hamsters at the age of 30 weeks and with the weight of ~100 g were used for the MRI experiments (n=6).…”
Section: Experimental Animal Modelmentioning
confidence: 99%
“…It is little known about the main source and proportion of nutrients for O . felineus [ 37 , 64 ], but liver flukes inhabiting the bile ducts are likely able to uptake nutrients from the bile. Young et al reported [ 65 ] that closely related species O .…”
Section: Discussionmentioning
confidence: 99%
“…166 “About fisheries and conservation of water biological resources” from 20.12.2004. For the experiment, 5-week-old male hamsters (n = 8) ( Mesocricetus auratus ) were infected intragastrically with 50 metacercariae per hamster, according to the previously described protocol [ 37 ]. Age-matched intact male hamsters (n = 8) were used as controls.…”
Section: Methodsmentioning
confidence: 99%